Translating proteome and transcriptome dynamics of periodontal ligament stem cell-derived secretome/conditioned medium in an in vitro model of periodontitis - Han Na Suh; Ju Young Ji; Jung Sun Heo (BMC, 2024)
Abstract Background Periodontal ligament stem cells (PDLSCs) have been proposed as therapeutic candidates in periodontal diseases and periodontium defects. Paracrine factors of PDLSCs, namely, secretome, can contribute to tissue regeneration comparable to direct stem cell application. This study explored restoration effects of PDLSC-derived secretome/conditioned medium (PDLSC-CM) on PDLSCs themselves in an inflammatory microenvironment and identified its action mechanisms using proteomics and transcriptomic profiling. Methods PDLSC-CM was prepared from cells under healthy culture conditions. Mass spectrometry and liquid chromatography-tandem mass spectrometry (LC-MS/MS) were then performed to analyze the PDLSC-CM proteome. Osteogenic differentiation of PDLSCs under inflammatory conditions or in the presence of PDLSC-CM was then characterized in assays of alkaline phosphatase activity, intracellular calcium levels, protein expression of osteogenic markers, and matrix mineralization. Furthermore, the transcriptomic profile was assessed to identify significantly enriched signaling pathways and associated molecular networks by RNA sequencing. Results LC-MS/MS proteomics identified a total of 203 proteins and distinguished 187 significant protein changes in PDLSC-CM compared to control-CM. LPS-treated PDLSCs significantly attenuated osteogenic differentiation. When PDLSCs were treated with PDLSC-CM alone, their osteogenic activity was significantly upregulated compared to the control group. Moreover, the LPS-impaired osteogenesis of PDLSCs was reconstituted by PDLSC-CM treatment. RNA sequencing revealed 252, 1,326, and 776 differentially expressed genes in the control vs. LPS, control vs. PDLSC-CM, and LPS vs. LPS + PDLSC-CM groups, respectively. Conclusion This study suggest that PDLSC-CM restores the osteogenic potential of PDLSCs in an inflammatory environment through secretory functions representing potential repair and regenerative mechanisms.